ANALISIS PENGARUH KOMISARIS INDEPENDEN, REPUTASI AUDITOR, KONSENTRASI KEPEMILIKAN DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Kartiko Dewi Pangestuti, 13.05.52.0194; Susilowati, Yeye (Students Journal of Accounting and Banking, 2018)
This study examines the effect of independent commissioner, auditor reputation, ownership concentration, and the firm size to enterprise risk management disclosure. This reseach was conducted at the Indonesian Stock Exchange by using analysis unit manufacturing companies that have gone public. The sampling method using purposive sampling the study periode of 2014 through 2016. The analysis technique that used is multiple regression analysis using SPSS 21. As a condition for statistical testing has been done normality test and classical assumption that the result show that distribution is the norm and escaped from the classical assumptionThe result showed that independent commissioner, ownership concentration, and the firm size does not effect Enterprise Risk Management disclosure, while auditor reputation positive effect Enterprise Risk Management disclosure.Keywords : enterprise risk management, independent commissioner, auditor reputation, ownership concentration, and firm size.